Análisis jurídico del capítulo iii (reformas a la ley de seguridad social: cesantía y seguro de desempleo) de la “ley orgánica para la promoción del trabajo juvenil, regulación excepcional de la jornada de trabajo, cesantía y seguro de desempleo - Sánchez Amores, Igor Tolstoy (2017)
Social security is a right that attends all people , since its purpose is to reduce the risks and vulnerabilities faced by mainly the most marginalized social groups , to achieve somehow achieve minimum levels of dignity of life for all citizens and try to correct the imbalances of wealth and opportunities that are inevitable in all societies. One of the demonstrations that pays social inequality is precisely unemployment, which marginalizes large masses of the population of the opportunity to access a decent life. That is why I considered it important to analyze the system of protection that our country has implemented to protect the phenomenon of unemployment , with particular attention to recent changes , their strengths and weaknesses , and present a proposal to improve its functioning .